2011
DOI: 10.1093/humrep/deq333
|View full text |Cite
|
Sign up to set email alerts
|

Do polymorphic variants of chromosomes affect the outcome of in vitro fertilization and embryo transfer treatment?

Abstract: BACKGROUNDThe aim of this study was to investigate the effect of chromosomal polymorphic variations on the outcome of IVF and embryo transfer (IVF–embryo transfer) treatment for infertile couples.METHODSDuring the period from October 2006 to December 2009, 1978 infertile couples who had received their first IVF–embryo transfer treatment cycle in our hospital were selected for this retrospective study, and the frequency of chromosomal polymorphic variations was calculated. From these, 1671 couples were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(116 citation statements)
references
References 19 publications
10
102
1
3
Order By: Relevance
“…Chromosome abnormalities and polymorphisms were reported according to the International System for Human Cytogenetic Nomenclature (ISCN, 2009) (Shaffer and Slovak, 2009). It is worth noting that the pericentric inversion of chromosome 9 [inv (9)] was also considered to be as a polymorphism (Hong et al, 2011) in this study.…”
Section: Karyotype Analysismentioning
confidence: 99%
“…Chromosome abnormalities and polymorphisms were reported according to the International System for Human Cytogenetic Nomenclature (ISCN, 2009) (Shaffer and Slovak, 2009). It is worth noting that the pericentric inversion of chromosome 9 [inv (9)] was also considered to be as a polymorphism (Hong et al, 2011) in this study.…”
Section: Karyotype Analysismentioning
confidence: 99%
“…The results of Madon et al, (2005) evaluated 842 individuals attending an IVF clinic with primary infertility or repeated miscarriages, showed polymorphic variants in 28.82% of males and 17.19% of females5. Hong et al, (2011) studied the effect of polymorphic variants in the outcome of in vitro fertilization on 1978 couples and found 182 males presented with chromosomal variations (9.2%). There was no any difference found among observed implantation rates but the incidence of first trimester pregnancy loss was higher compared to couples with normal karyotype (Hong et al, 2011).…”
Section: Brothman Et Al (2006) Reported the Survey Results Of The Cmentioning
confidence: 99%
“…Hong et al, (2011) studied the effect of polymorphic variants in the outcome of in vitro fertilization on 1978 couples and found 182 males presented with chromosomal variations (9.2%). There was no any difference found among observed implantation rates but the incidence of first trimester pregnancy loss was higher compared to couples with normal karyotype (Hong et al, 2011). Minocherhomji et al, (2009) in the casecontrol study identified a highly statistically significant increase in the frequency of total chromosomal variants in infertile women (28.31% vs. 15.16%) and infertile men (58.68% vs. 32.55%) as epigenetic alterations associated with the infertility phenotype8.…”
Section: Brothman Et Al (2006) Reported the Survey Results Of The Cmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that some chromosomal polymorphisms can be associated with habitual miscarriage, developmental early pregnancy loss, stillbirth, poor maternal history and cacospermia [6]. genes associated with spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%